How to manipulate friends and influence practice: Application of complexity science leads to quality improvement in laboratory sample submissions. Issue 2 (March 2019) - Simmons, Mike; Daniel, Sharon; Temple, Mark
Background: We sought to reduce healthcare-associated infections (HCAIs) through the application of complexity science. Objective: To confirm incidental findings that altering the structure of microbiology reports with targeted education led to better utilisation of laboratory resources, while participating in efforts to reduce HCAI. Methods: We adopted a different approach to laboratory result authorisation, using narrative to engage the clinicians and induce behavioural change. Subsequent educational opportunities emphasised key messages. Findings/Results: Positive urine means calculated by the analysis tool numbered 2179/month throughout the study period. Negative urines started at 5576/month, reduced to 5134/month in November 2014 and to 4602/month in April 2016, coinciding with our changes. Opportunity costs were saved. Discussion: The changes in both policy and reporting were contemporaneous with a decline in negative samples. There were no significant changes in the number of positive specimens. The efficiency and effectiveness of the laboratory was improved and resources released: £145, 000 ($182, 000) for a resident population of 384, 000. This suggests an annual release of about £25 million ($31 million) may be possible in the UK and £122 million ($155 million) in the USA.